Improved electrochemical activity of the Li2MnO3-like superstructure in high-nickel Li-rich layered oxide Li1.2Ni0.4Mn0.4O2 and its enhanced performances via tungsten doping. (20th February 2021) - Guo, Limin; Tan, Xinghua; Mao, Dongdong; Zhao, Tingqiao; Song, Luting; Liu, Yanlin; Kang, Xiaohong; Wang, Hanfu; Sun, Lianfeng; Chu, Weiguo
Highlights: W is doped into the lattice of Li1.2 Ni0.4 Mn0.4 O2 HNLR oxide to replace part of Mn. The superstructure is improved leading to enhanced oxygen redox reversibility. The primary particle sizes are reduced resulting in enhanced kinetics. Capacity, ICE and rate capability of the HNLR oxide are significantly improved. Abstract: Voltage decay of Li- and Mn-rich layered oxides can be effectively suppressed by increasing their Ni contents, which however normally results in a sizable decrease in capacity probably due to the reduced Li2 MnO3 -like superlattice component. Here, we reveal that the partial replacement of Mn by W in the high-nickel Li-rich (HNLR) layered oxide Li1.2 Ni0.4 Mn0.4 O2 leads to the increase in both Li2 MnO3 -like superlattice component and Ni 2+ proportion due to the presence of W 6 + . As a result, the doping of W favors the activation of the Li2 MnO3 -like component with the reversible redox of more oxygen anions and the creation of a multi-cation chemical environment, accompanied by the size reduction of primary particles and the increase in lattice parameters. The reversible redox of more oxygen anions results in much higher capacity and initial Coulombic efficiency. The reduced sizes of primary particles, along with the lattice expansion significantly enhance the electrochemical kinetics, which accounts for superior rate capability and excellent high-rate cycling performance. This study opens a possibility of improving the performance of HNLR oxides by doping appropriate elements to modify and optimize the properties of the Li2 MnO3 -like component.